Teaching practices and the need to renew pedagogical resources in Geography classes-As práticas docentes e a necessidade da renovação dos recursos pedagógicos nas aulas de Geografia - Maria Camila Nunes da Silva (Diversitas Journal, 2020)
Teaching practices with the advancement of technology and the creation of trends of the current period generate the need for the renewal of pedagogical resources in geography classes. The main objective is to discuss the possibility of renewal of the pedagogical resources necessary for the lessons of geography. The methodological procedures take place in a qualitative way with a theoretical basis in readings of writers who discuss this subject, such as: Demo (2004), Trindade et al (2007) and Libâneo (2004) questionnaires to teachers and school staff to better detail the object under investigation. Files of the main works were used to facilitate the construction of the theoretical foundation, avoiding the need for rereading. The results show that there is a need for adequate resource the current demands, to better use of teaching in geography classes. However, the lack of pedagogical resources can reduce the possibilities of providing more interactive classes. It is concluded that, there is a strong need for investment in pedagogical, structural and financial resources teachers.